2022
DOI: 10.3389/fimmu.2022.854327
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Host Protein Biomarkers by ELISA From Whole Lysed Peripheral Blood for Development of Diagnostic Tests for Active Tuberculosis

Abstract: Tuberculosis (TB) remains a significant global health crisis and the number one cause of death for an infectious disease. The health consequences in high-burden countries are significant. Barriers to TB control and eradication are in part caused by difficulties in diagnosis. Improvements in diagnosis are required for organisations like the World Health Organisation (WHO) to meet their ambitious target of reducing the incidence of TB by 50% by the year 2025, which has become hard to reach due to the COVID-19 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…According to Shahin Ranjbar et al (24), IFITM3 overexpression inhibits the growth of Mycobacterium tuberculosis growth in these cell types, whereas knockdown of IFITM3 expression reduction signi cantly promotes Mycobacterium tuberculosis in monocytes, providing evidence for the involvement of antiviral IFITM3 in the restriction of Mycobacterium tuberculosis. Good diagnostic performance has also been demonstrated by IFITM3 in studies of biomarkers of pulmonary tuberculosis (25). In addition, several other studies have reported the correlation of IFITM3 with Alzheimer's disease (26) and some tumors (27).…”
Section: Discussionmentioning
confidence: 90%
“…According to Shahin Ranjbar et al (24), IFITM3 overexpression inhibits the growth of Mycobacterium tuberculosis growth in these cell types, whereas knockdown of IFITM3 expression reduction signi cantly promotes Mycobacterium tuberculosis in monocytes, providing evidence for the involvement of antiviral IFITM3 in the restriction of Mycobacterium tuberculosis. Good diagnostic performance has also been demonstrated by IFITM3 in studies of biomarkers of pulmonary tuberculosis (25). In addition, several other studies have reported the correlation of IFITM3 with Alzheimer's disease (26) and some tumors (27).…”
Section: Discussionmentioning
confidence: 90%
“…Table 1 shows the performance of each marker and the summary of study quality. Eighteen markers met TPP in HIV-negative patients: CALCOCO2 (21), CD14 (22), CRP (23), Ferritin (24), GBP1 (21), HO-1 (25, 26), IFIT3 (21), IFITM3 (21), IP-10 (18), MMP-1 (19), OPN (27), PD-L1 (21), SAA (25), SAMD9L (21), SELL (22), SNX10 (21), TIMP-2 (19), and TIMP-4 (28). All of these studies had a high overall risk of bias due to the use of LTBI or healthy control groups in the absence of patients with ORD.…”
Section: Resultsmentioning
confidence: 99%
“…A combination of HO-1 and MMP-1 using participants with LTBI as the comparator group was reported separately by sites in Brazil and India (26). A three-marker signature of CALCOCO2, IFITM3, and SAMD9L tested lysed whole blood with ELISA, comparing TB cases in India to asymptomatic contacts from India and the United Kingdom (21). The four-marker signature of CLEC3B, ECM1, IP-10, and SELL used Luminex to test plasma samples from TB cases and LTBI controls in Madagascar (22).…”
Section: Resultsmentioning
confidence: 99%
“…These tests show less effectiveness in comparison with IGRA tests [23,44]. In this connection, the search for new or additional biomarkers for TB diagnosis with greater information content continues [50,51].…”
Section: Discussionmentioning
confidence: 99%